The Implementation of Project Based Learning to Teach Speaking - Aryarta, Anggih Restu; Saraswati, Girindra Putri Dewi (Universitas Negeri Semarang, 2024)
Learning model is one of the important tools to transfer material by teachers to students in the classroom. Until this 21st century, many learning models have been created and developed which aim to facilitate learning in the classroom to be well organized and achieve the learning objectives themselves. This research aims to analyze the implementation of Project Based Learning (PJBL) learning model in teaching speaking. This research was conducted qualitatively with Milles, Huberman, and Saldana (2014) qualitative description model. Data collection in this study used observation, interview, and document collection methods, while the research participant of this study was one of the language classes that used the PJBL learning model in teaching speaking and three language teachers. The researcher chose a sample of one class IX at SMP Negeri 11 Semarang as the material and place of research. The validation of the instrument used by the researcher has been validated by educational expert with doctoral qualifications. The research findings showed that the language classes in SMP Negeri 11 Semarang had implemented the PJBL learning model in accordance with the instrument that became the research reference in the form of characteristics and steps of the PJBL learning process. However, the researcher also found problems in the learning process that can be handled collaboratively by students with teacher guidance.